Application of novel metal–organic frameworks containing sulfonic acid pendings in synthesis of chromeno[4,3-d]pyrimidines via back to back anomeric based oxidation - Fatemeh Jalili; Hassan Sepehrmansourie; Mahmoud Zarei; Mohammad Ali Zolfigol; Ardeshir Khazaei; Mohammad Ali As'Habi (Arabian Journal of Chemistry, 2024)
Through task-specific design and synthesis of mesoporous catalysts, we introduce a novel metal–organic framework serving as a heterogeneous catalyst. In this study, Co(BDC-NH(CH2)3SO3H was meticulously prepared through the condensation reaction of 1,4-butane sultone and Co(BDC-NH2) utilizing a post-modification method. The thorough examination of these parameters ensures a detailed understanding of the catalyst's properties. Subsequently, the catalytic activity was explored in the synthesis of chromeno[4,3-d]pyrimidine derivatives employing a cooperative vinylogous anomeric-based oxidation mechanism. This research not only presents a new and efficient catalyst but also contributes valuable insights into the synthesis of biologically relevant chromeno[4,3-d]pyrimidine derivatives.